REVIEW OF METHODS USED FOR COVID-19 TIME SERIES FORECASTING OF DAILY CASES, DEATHS CAUSED AND RECOVERED CASES - Miss. Saloni Bharat Gangar; Prof. Dr. (Mrs.) Pratibha S. Yalagi-Kaladeep (International Journal of Innovations in Engineering Research and Technology, 2022)
The COVID-19 has been declared as a global pandemic by WHO, it has been considered as the most hostile disease, impacting more than ninety percent countries of the world. This virus was started from a lone human being in Peoples Republic of China, it is now growing globally. Some of the studies predicted that this virus will hang about with us everlastingly. India as a second most crowded country in the world is also under threat. Consequently, it has become truly important to investigate the possible blow of COVID-19 in India and to forecast how it will act in the upcoming days. This paper deals with the literature review of the various research works done by researchers all over the world for use of mathematical and statistical method to predict the Covid-19 new case, death cases and recovered cases. The work presented here is an attempt to find the most suitable and accurate method to obtain the objective as stated above.